Study of odorant compounds and sensory changes associated with wine spirit ageing using chestnut wood and Limousin oak under different technologies - Caldeira, Ilda (2022)
Wine spirit, resulting from wine distillation, usually undergoes ageing in wood before being marketed. Traditionally, the oak wood, especially from the French region of Limousin (mostly Quercus robur L.), is used for manufacturing the barrels for this purpose.